ANALISIS STRATEGI KOMUNIKASI PUSKESMAS KEDURUS BERSAMA POSYANDU DALAM PENCEGAHAN STUNTING DI KELURAHAN KEDURUS - Tezrah Santoso, Dwita; Alfraita, Ariyan; Widiyani Roosinda, Fitria (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2025)
This study analyzes the communication strategy of the Kedurus Community Health Center and Posyandu in preventing stunting in Kedurus Village. Stunting remains a major public health issue in Indonesia, particularly among young children, and is linked not only to medical factors but also to public awareness of nutrition and maternal health. Using a descriptive qualitative method, data were collected through observation and interviews with health center staff. The findings reveal that a key communication barrier is the public’s misperception—believing that a child who appears healthy does not face growth issues. The study concludes that effective stunting prevention communication relies on the ability of health workers and Posyandu cadres to build trust, deliver clear messages, and actively engage the community.